Avoid, Adopt, Adapt: Positions on GenAI in Canadian Writing Centres - Saunders, Gillian; Boldt, Natalie (Discourse and Writing/Rédactologie, 2025)
Generative Artificial Intelligence (GenAI) tools are transforming academic writing support in higher education, but student- and public-facing messaging from Canadian universities, and subsequently their writing centres, has been slow and inconsistent (Cheatle, 2025; Marcel & Kang, 2024; UNESCO, 2024). In the summer of 2024, two writing centre advisors conducted an environmental scan of writing centre websites and publicly available materials related to messages about GenAI literacy support. Documents were collected and assessed for 1) a “statement” or “policy” on GenAI use and assistance in the writing centre and 2) a stance toward using GenAI for writing, which we categorized broadly as able to assist with GenAI writing concerns (i.e., adopt) or disavowing use or assistance in the writing centre (i.e., avoid). Environmental scans facilitate discovery of opportunities and threats during times of change in the interest of making decisions and plans for the future. Our scan provides a snapshot of how writing centres, as well as the institutions they operate within, are positioning themselves within the current GenAI post-secondary landscape. This article contextualizes results within the current post-secondary landscape and offers recommendations and implications for the conceptualization of writing centre work.